A mixed methods scoping review of gender and life stage as risk factors of injury-related mortality in the Western Cape, South Africa - Voegt, Chelsey (Department of Human Biology, 2025)
Injury-related mortality is a growing public safety concern in South Africa, especially in the Western Cape Province. Several studies have identified gender and age as risk factors of injury related mortality, although there remains a scarcity of interstudy comparisons of these factors, and the underlying perceptions of causes linked to these. In this study, a scoping review of injury-related mortality from medicolegal death investigations in the Western Cape was conducted by screening online databases for research articles published between 2007 and 2021. Of the 11 articles, six were included in a quantitative analysis to quantify risk by gender and life stage. To assess conceptualisations of these risk factors in research, each article was evaluated using a thematic content analysis. Men were associated with a higher mortality risk for homicide (inclusive of sharp force and firearm causes), suicide, road traffic (and transport-related) deaths, and drowning. The likelihood of homicidal deaths in males (OR = 3.95; 95% CI [3.48 – 4.49]; p ≤ 0.001) was higher than all other causes of injury-related mortality (OR = 0.25; 95% CI [0.22 – 0.29]; p ≤ 0.001). For all causes of injury-related mortality, early adults (20 – 34 years) and middle-aged adults (35 – 49 years) accounted for the most deaths. Homicide was the most significant cause of mortality in early adults, adolescents and middle-aged adults, while road traffic deaths were the leading cause of mortality for infants and children and adults above 49 years of age. Qualitative results from the thematic content analysis suggest that the discourse of violence and injury in the literature differed by gender. Women were more commonly discussed with reference to vulnerability and victimhood. Contrastingly, men were portrayed with reference to culpability – regardless of whether they were victims or perpetrators of violence. Masculinity as a cause of violence, in the literature, was discussed relative to socio-economic conditions and cultural norms leading to risk-taking behaviours. Limited agency and lifestyle behaviours were described as primary causes of violence linked to life stage. Risk of injury in minors was attributed primarily to structural causes of violence, and cognitive reasoning and development linked to life stage. Overall, these results highlight gender-linked biases in forensic death reporting. Injury related deaths and homicides affected more males, yet males were primarily represented as perpetrators of violence. Given the drive to eradicate gender based-violence, this study emphasises the need to address structural causes of violence targeted at expressions of masculinity, social cohesion and identity in different life stages, and genders and the need for an intersectional approach to understanding medicolegal death investigations and injury-related mortality in the Western Cape and South Africa.